Genetic etiologies associated with non‐immune hydrops fetalis delineated by whole exome sequencing: A pilot series and its implications in prenatal genetic counseling - Lim, Zhu Wei; Ma, Gwo‐Chin; Chang, Ting‐Yu; Wu, Wan‐Ju; Lee, Mei‐Hui; Chen, Ming (The journal of obstetrics and gynaecology research, 2025)
Aim Non‐immune hydrops fetalis (NIHF) is a spectrum of disease involving heterogeneous etiologies. Prenatal application of whole exome sequencing (WES) has emerged as a valuable tool to decipher genetic causes in structural abnormalities detected by fetal ultrasound. Here, we reviewed index cases of NIHF whose genetic etiologies were delineated by WES. Methods We conducted a retrospective study on our pilot series (n = 12) of NIHF that underwent WES with outcomes systematically reviewed. For each case, we performed a detailed sonographic examination for anasarca, virology profile, karyotyping, and chromosomal microarray analysis (CMA), in addition to WES performed either prenatally or postnatally. Results Between December 2019 and July 2024, 12 fetuses with abnormal fluid accumulation in fetal compartments, despite normal karyotyping and CMA, underwent WES to elucidate potential genetic etiologies. Variant interpretation was performed in accordance with the guidelines of the American College of Medical Genetics and Genomics (ACMG). A definitive molecular diagnosis was established in all 12 cases, with identified disorders including lymphatic abnormalities (33%), musculoskeletal disorders (30%), and syndromic conditions (17%). All recurrent cases (3/3, 100%) and those who received fetal therapy (4/4, 100%) have a definite molecular diagnosis. Two survived fetuses were diagnosed in the first and third trimesters, respectively, while four infants died and six couples decided to terminate the pregnancy due to disease progression. Two novel founder variants (HSPG2 and BBS2) were found. Conclusion WES is an effective tool to determine the genetic diagnosis of NIHF cases and would discover more novel causative genes to match the prenatal phenotypes exhibited.